Conflict styles regarding payment role among Finnish-Chinese intercultural couples - Wang, Qingwen (2019)
This study looks at the way Finnish-Chinese intercultural couples discuss payment roles in the context of their relationship. The study seeks to increase our understanding of the impact of different cultural identities in intercultural romantic relationships. The present study used a qualitative approach to explore how intercultural couples negotiate possible conflicts regarding a specific topic: payment role. The theoretical framework of the study builds on the face negotiation theory. To be more specific, the study investigates how partners perceive cultural identities as influencing the concept of “face,” and their choice of conflict management styles. The present study highlights the importance of a direct and open communication style, as an efficient solution to disagreements or conflicts in intercultural relationship regarding sensitive issues like payment role, especially when two parties hold different origin cultural backgrounds. The findings show that both Chinese and Finnish participants are prone to adopt a low context communication style when they are confronting disagreements or conflicts in the relationships. This study implements face negotiation theory in the context of practical issues. The study may give ideas for future research and provide practical references for intercultural couples.